Originally Posted by

**dankelly07** im having problems again with the constant at the end!! just need a bit of help trying to figure it out..

$\displaystyle

\frac{d^2 y}{dx^2 } - 8 \frac{dy}{dx} + 7y = 0

$

$\displaystyle

(\lambda - 1)(\lambda - 7) = 0

$

$\displaystyle \lambda = 1 , \lambda = 7

$

$\displaystyle y(x) = Ae^x + Be^{7x}$

$\displaystyle 0 = A + B

$

$\displaystyle 5 = y'(0)

$.....

Its just this last part with the constant here I'm strugging with can someone help finish this off..

I know the answer it should be,

$\displaystyle

y = \frac{5}

{6}(e^{7x} - e^x )

$